Fluid Resuscitation in Trauma - Kun Arifi Abbas (Faculty of Medicine-Universitas Airlangga, 2019)
Introduction: Trauma is a problem faced everyday in the emergency room of the hospital where the researcher works. The degree of trauma from the mildest to life threatening can be found in sufferers. The cause of death in trauma sufferers is hypovolemic shock due to bleeding. The amount of blood loss volume from the patient can be estimated by looking at the clinical signs of the patient. Literature Review: In the condition of tissue hypoperfusion, it will cause a chain process which will eventually lead to cell death. Hypoperfusion causes anaerobic metabolism, lactic acidosis (coagulopathy, enzyme dysfunction), Na-K pump malfunction (cellular swelling and cell death), there is hypothermia (increase of oxygen demand, coagulopathy). Hypoperfusion will cause a vicious circle, in which processes that aggravate one another will occur. With the administration of fluids (crystalloid, colloid, transfusion) will improve the hypoperfusion that occurs in the body. Conclusion: The management of hypovolemic shock due to bleeding requires an understanding of the physiology and pathophysiology that occurs due to bleeding. To get maximum results and improve outcome from sufferers, it needs solid team work. Treatment can be different depending on the conditions, equipment and facilities of the hospital / emergency room as well as the policies of each place.